Antilisterial and Antibiofilm Activities of Pediocin and LAP Functionalized Gold Nanoparticles - Singh, Atul K.; Bai, Xingjian; Amalaradjou, Mary Anne Roshni; Bhunia, Arun K. (Frontiers in Sustainable Food Systems, 2018)
In this study, we synthesized and assessed the antilisterial and antibiofilm properties of a novel gold nanocomposite, functionalized with antimicrobial peptide, Pediocin AcH and Listeria adhesion protein (LAP) for targeted inactivation of L. monocytogenes. The gold nanoparticle (GNP) and the gold nanocomposites (GNP-Pediocin-LAP) were characterized using spectroscopic and transmission electron microscopy (TEM) and their effect on human enterocyte-like Caco-2 cells were assessed by lactate dehydrogenase (LDH)-based cytotoxicity and inhibition of Listeria adhesion assay. The antilisterial and antibiofilm activities of nanocomposites on L. monocytogenes were determined by a plating method. TEM image analysis indicated that the size of GNP and the gold nanoconjugates to be about 20 and 40 nm, respectively; and spectroscopy indicated the successful loading of proteins onto citrate-stabilized GNPs. Gold nanocomposites were non-toxic and significantly reduced L. monocytogenes adhesion to Caco-2 cells. Relative to the GNP-Pediocin conjugate, the GNP-Pediocin-LAP conjugate showed 11.1% higher zone of inhibition in agar diffusion assay, and higher reduction (1.5 log10 CFU/mL) in L. monocytogenes counts. Same preparation also showed 24 and 31% more reduction in Listeria counts in biofilms after 24 and 48 h of incubation, respectively. Nanocomposites were also highly effective in decontamination of L. monocytogenes on a miniature industrial conveyor system. Altogether, co-action of Pediocin and the LAP functionalized on GNP (GNP-Pediocin-LAP), demonstrated higher antilisterial and antibiofilm activities compared to the Pediocin functionalized GNP or Pediocin alone suggesting GNP can provide a platform to load multiple proteins for surface decontamination of L. monocytogenes in industrial settings.